2005
DOI: 10.1021/jf049001r
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Tests to Assess the Antioxidant Activity of Phaseolus vulgaris L. Dry Beans

Abstract: The antiradical activity of dry beans was evaluated in order to assess the validity of this test and to correlate the results with those achieved with the Folin-Ciocalteu method and with a rapid spectrophotometric method for the analysis of total flavonoids. Four landraces (12 samples) of common beans (Phaseolus vulgaris L.), collected in two regions of Italy (Tuscany and Basilicata) in three different years, were analyzed. The EC50 values ranged from 39 to 2810 mg sample/mg 1,1-diphenyl-2-picrylhydrazil radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
173
5
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(189 citation statements)
references
References 24 publications
5
173
5
6
Order By: Relevance
“…TPC in whole chickpea seeds was determined on a dry matter basis using the Folin-Ciocalteu assay [25,26] and TFC was determined using a colorimetric method [6] in 50-μl extraction samples, as previously described [22]. The FRAP method was used to evaluate the antioxidant activity of chickpea extracts, by measuring the ferric reducing ability of plasma at low pH levels [27] as previously described [22].…”
Section: Determination Of Tpc Tfc and Antioxidant Activity Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…TPC in whole chickpea seeds was determined on a dry matter basis using the Folin-Ciocalteu assay [25,26] and TFC was determined using a colorimetric method [6] in 50-μl extraction samples, as previously described [22]. The FRAP method was used to evaluate the antioxidant activity of chickpea extracts, by measuring the ferric reducing ability of plasma at low pH levels [27] as previously described [22].…”
Section: Determination Of Tpc Tfc and Antioxidant Activity Levelsmentioning
confidence: 99%
“…Dry legumes are a good source of bioactive polyphenols [4] and also contribute to polyphenol intake from other foods [5]. The antioxidant capacity [6] and the antimutagenic [7][8][9][10], apoptosis-related [11] and antiproliferative effects of legumes are associated with the presence of phenolic compounds [12,13]. The abundance of phenolic compounds in such legumes as the common bean (Phaseolus vulgaris) [9], faba (broad) bean (Vicia faba) [14,15], beach pea (Lathyrus maritimus) [16], Total Phenolic Content and Antioxidant Activity of Chickpea (Cicer arietinum L.) as Affected 725 by Soaking and Cooking Conditions mung bean (Vigna radiata) [17], lentil (Lens culinaris) [18] and chickpea (Cicer arietinum) [19][20][21][22] implies that they may be significant food sources of active antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…XU & CHANG (2007) found 1.53 to 7.53mg GAE g -1 for total phenolics and 1.40 to 8.78mg CAE g -1 for condensed tannin in 8 commonly consumed legumes. HEIMLER et al (2005) found 1.17 to 4.40mg of GAE g -1 for total phenolics in four landraces of common beans. These comparisons show wide variability for polyphenols (total phenolics, total flavonoids and condensed tannins) in the commonly cultivated accessions of P. lunatus conserved in the Brazilian genebank.…”
Section: Resultsmentioning
confidence: 90%
“…However, not all authors observed such a dependence. Heimler et al (2005), when analyzing the level of polyphenolics and antioxidant activity in beans over a period of three years, stated that beans, which are richest in such polyphenolic compounds as proanthocyanidins and fl avonoids, exhibited only medium antioxidant activity. The researchers were of the opinion that antioxidant activity is infl uenced by both the total amount of contained polyphenolics and the proportion of individual groups in the total pool of these substances.…”
Section: Antioxidant Activity Of Asparagus With Abts Radicalsmentioning
confidence: 99%